The impact of pharmacist-led education and prospective audit and feedback on antibiotic dose optimization within medical intensive care units in Thailand: a retrospective study - Tipanong Gatechan; Chotirat Nakaranurack; Rongpong Plongla; Thanawan Chuenjit; Alan Edward Gross (Journal of Pharmaceutical Policy and Practice)
Background Critical illness can affect antimicrobial pharmacokinetics and pharmacodynamics. Antimicrobial stewardship programs promote appropriate antimicrobial usage. This study aimed to compare the appropriateness of antibiotic dosing, therapeutic drug monitoring, and ICU mortality before and after antimicrobial stewardship program implementation in medical intensive care units.Methods This retrospective study was conducted at King Chulalongkorn Memorial Hospital, Thailand. Adults admitted to medical intensive care units from August 1, 2019, to July 31, 2021, who received selected antibiotics in the antimicrobial stewardship program were included. During the intervention period, general education as well as prospective audit with intervention and feedback were implemented by infectious disease pharmacist and clinical pharmacists. The appropriateness of dosing, therapeutic drug monitoring, and ICU mortality were compared before and after antimicrobial stewardship program implementation.Results There were 269 patients (455 prescriptions) and 376 patients (604 prescriptions) in the pre- and post-antimicrobial stewardship program implementation groups, respectively. Meropenem was the commonly prescribed antibiotic in both groups. Overall, the appropriateness of dosing and therapeutic drug monitoring improved after antimicrobial stewardship program implementation (36% to 63.58%, p < 0.001). Infectious disease and clinical pharmacists provided 40 interventions with an 87.5% acceptance rate. The most common recommendation was maintenance dose adjustment (79.17% acceptance rate). ICU mortality (29.37% to 18.62%, p = 0.001) and length of hospital stay in the ICU (7 days to 5 days, p = 0.005) were lower in the post-antimicrobial stewardship program implementation group.Conclusions Pharmacist-led education and prospective audit and feedback on antibiotic dose optimization can improve appropriate antibiotic dosing and therapeutic drug monitoring with a high acceptance rate. We suggest implementing this strategy in other intensive care units such as surgical intensive care units. We still found some nonadherence to our dosing guidelines; additional strategies to optimize dosing should be evaluated.